2019
DOI: 10.1021/acsbiomaterials.9b00887
|View full text |Cite
|
Sign up to set email alerts
|

Silkworm Silk Scaffolds Functionalized with Recombinant Spider Silk Containing a Fibronectin Motif Promotes Healing of Full-Thickness Burn Wounds

Abstract: Full-thickness cutaneous wounds, such as deep burns, are complex wounds that often require surgical interventions. Herein, we show the efficacy of acellular grafts that can be made available off-theshelf at an affordable cost using silk biomaterials. Silkworm silk fibroin (SF), being a cost-effective and natural biopolymer, provides essential features required for the fabrication of three-dimensional constructs for wound-healing applications. We report the treatment of third-degree burn wounds using a freeze-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Moreover, wound healing effects were evaluated in murine models for up to 28 days and the patch showed the fastest wound healing effect and resulted in a smooth epidermal layer compared with the other two groups (Figure A,ii). Meanwhile, Mandal et al designed a freeze-dried microporous fibronectin motif (FN-4RC)-coated spider silk scaffold for dealing with third-degree deep burns . It was demonstrated that in contrast to the uncoated counterpart, the scaffold displayed high wound closure efficiency in an in vivo rat burn model within 14-day treatment benefiting from the biological activity of the spider silk fusion protein in the scaffold, as shown in Figure B.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, wound healing effects were evaluated in murine models for up to 28 days and the patch showed the fastest wound healing effect and resulted in a smooth epidermal layer compared with the other two groups (Figure A,ii). Meanwhile, Mandal et al designed a freeze-dried microporous fibronectin motif (FN-4RC)-coated spider silk scaffold for dealing with third-degree deep burns . It was demonstrated that in contrast to the uncoated counterpart, the scaffold displayed high wound closure efficiency in an in vivo rat burn model within 14-day treatment benefiting from the biological activity of the spider silk fusion protein in the scaffold, as shown in Figure B.…”
Section: Applicationsmentioning
confidence: 99%
“…(B) Re-epithelialization assessment of wounds on days 14 and 21 by IHC assay for a freeze-dried microporous FN-4RC-coated spider silk scaffold. Reprinted with permission from ref . Copyright 2019 American Chemical Society.…”
Section: Applicationsmentioning
confidence: 99%
“…112 Similarly, further progress was achieved by adding endothelial cells (ECs) along with fibroblasts, which generated prevascularized skin grafts in a facile manner. 63,113 Further advancement in this field can be seen in stem cell 114−116 The advantages and disadvantages of the application of these stem cells as therapeutics are enlisted in Table 2. In a recent report, a well-established dermal graft, Integra, was used to culture human SGSCs that demonstrated enhanced vascularization in the regenerated dermal region.…”
Section: Need For Technological Advancements Over Conventional Therapiesmentioning
confidence: 99%
“…Silk, known for incisional wound healing in the form of silk sutures, has been found to trigger cell proliferation and cell migration via NF-KB signaling pathway in a recent study . The wound healing property of silk has been examined in various formats such as nanofibrous mats, thin films, hydrogels, and porous scaffolds, which have shown better healing properties in comparison to the commercially available products. , Electrospun silk nanofibrous nonwoven membranes showed a significant effect on cell attachment and spreading in vitro for normal human fibroblasts and keratinocytes . In further studies, three different forms of silk matrices, woven (microfiber), nonwoven (nanofiber), and regenerated film were utilized to perform a conformational analysis and cell culture using normal human oral keratinocytes (NHOK) .…”
Section: Silk: Biomedical Applicationsmentioning
confidence: 99%